Visionary Leadership of School Principals in Developing Institutional Quality Management - Fauzi, Muhammad Irfan; Aimah, Siti; Khaudli, Muhammad Imam (EDUTEC : Journal of Education And Technology, 2024)
Visionary leadership is characterized by leaders who possess a clear vision to achieve the organization's goals. This study is motivated by the current developments that demand school leaders to innovate and advance to compete with other educational institutions. The aim of this research is to explore the development of quality management at MTs Al-Furqon Pasir Sakti through the visionary leadership style of the school principal. This involves the creation, formulation, and implementation of the school vision, with the principal's role being pivotal. The objective is to become visionary leaders to advance the school and achieve high quality standards. This qualitative descriptive research involved the school principal, vice principals, teachers, and students. Data collection methods included interviews, observations, and documentation. Data analysis involved reviewing all data, data reduction, data presentation, and drawing conclusions. The findings indicate that the principal's visionary leadership in developing quality management at MTs Al-Furqon Pasir Sakti focuses on quality functions and management processes including planning, organizing, managing, monitoring, and evaluating. The steps in visionary leadership include: (1) Creating the school's vision and mission based on its ideals and contextual situation, (2) Formulating a unique and unprecedented vision, socializing the principal's ideas, and gathering feedback from all members, (3) Guiding and motivating the principal to realize the vision through concrete actions, and (4) Enhancing student capabilities and improving school quality. Consequently, MTs Al-Furqon Pasir Sakti has an excellent class program designed by the principal, taking into account the unique talents of the students.